ChemInform Abstract: Toward a More Complete Understanding of Noncovalent Interactions Involving Aromatic Rings. Issue 38 (10th September 2014) - Wheeler, Steven E.; Bloom, Jacob W. G.
Abstract Review: 147 refs.